USING DISCUSSION BOARD AS THE MEDIUM TO IMPROVE THE SKILL IN WRITING A RECOUNT TEXT - Lilis Sholihah (State Institute for Islamic Studies IAIN of Metro, 2013)
This study is aimed to improve the students’ skill in writing a recount text through the use of discussion board. The subject consists of twenty seven eighth graders. This study was carried out in one cycle. The cycle consisted of five meetings including the registration process on discussion board, prewriting and drafting in face to face classroom environment, and the process of revising, editing and publishing stage on discussion board. The data of the study were taken from the observation checklist, field notes, questionnaire and the students’ final product. The findings of the study revealed that the discussion board was successful in improving the skill in writing a recount text of the eighth graders. The improvement was indicated by the increase of the students’ writing scores, the students’ participation in writing activities and the students’ positive responses after the implementation of discussion board.